Volume microscopy: multiscale imaging with photons, electrons, and ions - Wacker, Irene; Hummel, Eric; Burgold, Steffen; Schröder, Rasmus R. (Springer US, 2020)
Correlative Super Resolution and Electron Microscopy to Detect Molecules in their Native Cellular Context -- Multi-Color Super-Resolution Microscopy: Revealing the Nano-World of Astrocytes In Situ -- High Resolution Molecular Imaging and Its Applications in Brain and Synapses -- Advancing Array Tomography to Study the Fine Ultrastructure of Identified Neurons in Zebrafish (Danio rerio) -- A Low-Tech Approach to Serial Section Arrays -- Large Volumes in Ultrastructural Neuropathology Imaged by Array Tomography of Routine Diagnostic Samples -- Correlative Ultrastructural Analysis of Functionally Modulated Synapses using Automated Tape-Collecting Ultramicrotome and SEM Array Tomography -- Large-Scale Automated Serial Section Imaging using a Multi-Beam Scanning Electron Microscope -- Improving Serial Blockface SEM by Focal Charge Compensation -- Using X-Ray Microscopy to Increase Targeting Accuracy in Serial Block-Face Scanning Electron Microscopy -- FIBSEM Analysis of Interfaces between Hard Technical Devices and Soft Neuronal Tissue -- Transforming FIB-SEM Systems for Large Volume Connectomics and Cell Biology -- Image Processing for Volume Electron Microscopy -- Forget about Electron Micrographs: A Novel Guide for using 3D Models for Quantitative Analysis of Dense Reconstructions.